PERAN BUMDes PANGGUNG LESTARI DALAM PEMBERDAYAAN MASYARAKAT DESA PANGGUNGHARJO, SEWON, BANTUL - Dating Sudrajat; Syakdiah Syakdiah; Suwarjo Suwarjo (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
Village-owned enterprises (BUMDes) are economic business entities formed by villages with a legal umbrella of PERDES and are supported operationally with village fund allocations (ADD). This study aims to determine the role and impact of BUMDes in community empowerment in Desa Panggungharjo, Sewon, Bantul. This research is a qualitative descriptive study. Primary data taken directly from respondents were then analyzed using descriptive analytic techniques. Data collection techniques through interviews, documents and observations. The results showed that the BUMDes Panggung Lestari had a very large role in community empowerment in the Village of Panggungharjo, Sewon, Bantul. The role of BUMDes in community empowerment is seen from the 5 variables including institutional improvement, improvement of community economic efforts, improvement of community income, environmental improvement, and social contributions made to the community. The BUMDes Panggung Lestari has a good and significant role in community empowerment